The Structuration Approach of Anthony Giddens - Lamsal, Mukunda (Himalayan Journal of Sociology and Anthropology, 2012)
Structuration Theory developed by Anthony Giddens, a British sociologist, in response to claims by post-structuralism, holds that the structures that humans find themselves in are determined for them, and volunteerism, that suggests that humans are completely free to create their lived environment. Structuration theory has a several unique nomenclature to explain the relationships that the human “agency” has with institutions or “structure”. This paper explains the use of the words and relates them to relevant examples. The understanding that Structuration Theory gives us can be very useful for understanding geographic phenomenon such as the idea of the time-space continuum. Urban arenas have a very complex set of relationships between humans and their environments; housing, movement within the environment, etcetera. The paper is also focused on understanding the connections between Giddens’ theory and the field of geography. The main focus of this paper is on exploring the complexities of Giddens’ Structuration Theory and understanding how it is currently being implemented in societies. DOI: http://dx.doi.org/10.3126/hjsa.v5i0.7043 Himalayan Journal of Sociology & Anthropology-Vol. V (2012) 111-122